Short-course intravenous antibiotics for young infants with urinary tract infection. Issue 10 (25th April 2022) - Lawrence, Jolie; Pittet, Laure F; Hikmat, Samar; Silvester, Eloise J; Clifford, Vanessa; Hunt, Rodney; Gwee, Amanda
Abstract : Objective: Shorter courses of intravenous antibiotics for young infants with urinary tract infection (UTI) have myriad advantages. As practice shifts toward shorter intravenous treatment courses, this study aimed to determine the safety of early intravenous-to-oral antibiotic switch and identify risk factors for bacteraemia with UTI. Methods: Retrospective audit of infants aged ≤90 days with a positive urine culture at a quaternary paediatric hospital over 4 years (2016–2020). Data were collected from the hospital electronic medical record and laboratory information system. Short-course intravenous antibiotic duration was defined as <48 hours for non-bacteraemic UTI and <7 days for bacteraemic UTI. Multivariate analysis was used to determine patient factors predicting bacteraemia. Results: Among 427 infants with non-bacteraemic UTI, 257 (60.2%) were treated for <48 hours. Clinicians prescribed shorter intravenous courses to infants who were female, aged >30 days, afebrile and those without bacteraemia or cerebrospinal fluid pleocytosis. Treatment failure (30-day UTI recurrence) occurred in 6/451 (1.3%) infants. All had non-bacteraemic UTI and one received <48 hours of intravenous antibiotics. None had serious complications (bacteraemia, meningitis, death). Follow-up audiology occurred in 21/31 (68%) infants with cerebrospinal fluid pleocytosis, and one had sensorineural hearing loss. Bacteraemia occurred in 24/451 (5.3%) infants, with 10 receiving <7 days intravenous antibiotics with no treatment failure. Fever and pyelonephritis were independent predictors of bacteraemia. Conclusion: Short-course intravenous antibiotics for <48 hours for young infants with non-bacteraemic UTI should be considered, provided meningitis has been excluded. Treatment failure and serious complications were rare in young infants with UTI. Abstract : This study aimed to determine the safety of early IV-to-oral antibiotic switch, and identify risk factors for bacteraemia with UTIs. Short course IV antibiotics for <48 hours for young infants with non-bacteraemic UTI should be considered, provided meningitis has been excluded. Treatment failure and serious complications were rare in young infants with UTI.